Historical Perspectives on the Epidemiology of Human Chagas Disease in Texas and Recommendations for Enhanced Understanding of Clinical Chagas Disease in the Southern United States. - Melissa N Garcia; Laila Woc-Colburn; David Aguilar; Peter J Hotez; Kristy O Murray (PLoS Neglected Tropical Diseases, 2015)
Chagas disease (Trypanosoma cruzi infection) has recently been identified as an important neglected tropical disease in the United States. Anecdotally referred to as a "silent killer," it leads to the development of potentially fatal cardiac disease in approximately 30% of those infected. In an attempt to better understand the potential of Chagas disease as a significant underlying cause of morbidity in Texas, we performed a historical literature review to assess disease burden. Human reports of triatomine bites and disease exposure were found to be prevalent in Texas. Despite current beliefs that Chagas disease is a recently emerging disease, we report historical references dating as far back as 1935. Both imported cases and autochthonous transmission contribute to the historical disease burden in Texas. We end by discussing the current knowledge gaps, and recommend priorities for advancing further epidemiologic studies and their policy implications.